ANALISIS PEMBELAJARAN ONLINE PADA PESERTA DIDIK KELAS VIII SMP NEGERI 13 PONTIANAK - Virga Caesaria; Indri Astuti; Yuline Yuline (Universitas Tanjungpura, 2021)
AbstractThe study aims is to find out class VIII SMP Negeri 13 Pontianak online learning. The problem on this study is “How does the online learning on class VIII SMP Negeri 13 Pontianak?”. The method used on this study was descriptive survey study. The sample of this research was 40 students of class VIII SMP Negeri 13 Pontianak. The technique used to gather the data of this study was through indirect communication technique using a questionnaire. The data were analyzed using percentage calculation. The data analysis shows that learning motivation reaches 62,31% categorized as “Moderate”, technological literation on online learning reaches 69,7% categorized as “Moderate”, interpersonal communication reaches 76,45% categorized as “Good”, collaboration ability reaches 64,3% categorized as “Moderate”, and self learning skill reaches 70,55% categorized as “Moderate”. Therefore, the conclusion of online learning on class VIII SMP Negeri 13 Pontianak is categorized as “Moderate”.Keywords: Collaboration Ability, Interpersonal Communication, Learning Motivation, Self Learning Skill, Technological Literation.